Hedging as a Multifunctional Phenomenon of Research / Popular Research Articles - Nemickienė, Živilė (Respectus Philologicus, 2015)
The paper analyses the versatile usage of hedges in medical academic texts and compares the (sub)genre peculiarities of the scientific research articles (RA) and science popularization articles (PRA). While comparing the two subgenres, the generalized three factors of strategies and functions influencing hedging usage were discriminated, i.e., the expectations of the discourse community, intentions, and shared background knowledge. The comparative analysis of RA and PRA aims at investigating the use of the multifunctional hedging device, and at the end the corpus of nearly 90 000 words and 20 articles has been comprised as a research database. A normative use of hedges in academic texts is treated as appropriate nowadays. The research focuses on the analysis of hedging strategies and functions. It stretched the borders of one function and analyses hedging as a pragmatic, semantic, social, and cognitive phenomenon in the field of epistemic modality. The hedge is viewed from the semantic, pragmatic, cognitive, and social perspectives. This article reviews the role and legitimacy of hedging producing deliberate elusiveness in scientific texts, interprets the cases of hedge uses, infers their functions and meaning. It as well discusses the vector of movement direction from the “author-centred rhetoric” to the “object-centred rhetoric” and vice versa. Hedging is interpreted in the frame of epistemic modality.
Keywords: Hedge; Epistemic Modality; Research; Popular Research Article